Perlindungan Hukum Terhadap Pemilik Hak Atas Satuan Rumah Susun Akibat Wanprestasi Dalam Penyerahan Unit Apartemen - Lee Weng Yeen, Jessica (JURNAL MINUTA, 2025)
This research aims to find out and understand the form of legal protection that can be given to IF as the owner of the rights to the house unit due to the default in handing over the unit by PT EPH. This research is normative juridical research using a statutory regulation and legal concept approach. The research results show that everyone has the right to obtain legal protection in carrying out buying and selling transactions for apartment units. The right to legal protection has been explicitly regulated in Article 28D paragraph 1 of the 1945 Constitution so that it must be provided by the state. In practice, the sale and purchase transaction of apartment units is an agreement based on Article 1457 BW. This apartment unit sale and purchase agreement will of course give rise to rights and obligations for each party involved. However, along the way, it is not uncommon for defaults to occur from one of the parties, namely the developer. This was experienced by Ike Farida who had paid off the purchase of the Apartment X unit. However, PT EPH actually made a unilateral cancellation and did not hand over the apartment unit that had been paid for by IF. As a result, IF suffered material and immaterial losses. Based on the court decision, IF is a buyer with good intentions and therefore deserves to be protected by law. Meanwhile, the legal protection that can be given to IF is compensation in accordance with Article 1243 BW. Apart from that, Ike Farida can also sue PT EPH through the institution tasked with resolving disputes between consumers and business actors or through courts within the general judiciary in accordance with Article 45 paragraph 1 of the Consumer Protection Law.